So schaffen wir das – eine Zivilgesellschaft im Aufbruch: Bedingungen für die nachhaltige Projektarbeit mit Geflüchteten. Eine Bilanz - Eilert, Anne; Rudloff, Marlene; Schiffauer, Werner (transcript, 2018)
Refugees in Germany: 2015 was the summer of projects. The civil society has proved to be extraordinarily creative while dealing with the challenges caused by migration and has positioned itself anew. Now the time has come to take stock: What has worked out; where and how could sustainability be achieved? What part did the successful collaboration of politics, administrative forces and civilians play in this? However, this book also examines the reasons why projects failed: How and why could the commitment of the participants not be kept up? In addition, the challenges that the increasing pressure from the right wing poses are discussed.